2011
DOI: 10.1111/j.1398-9995.2011.02637.x
|View full text |Cite
|
Sign up to set email alerts
|

The association between bacterial colonization and inflammatory pattern in Chinese chronic rhinosinusitis patients with nasal polyps

Abstract: Our findings suggest that the bacteria colonizing nasal polyps of CRSwNP patients may impact on or be determined by the presence/absence of IL-5.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
67
0
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(72 citation statements)
references
References 22 publications
2
67
0
3
Order By: Relevance
“…The association of albumin with eosinophil products can be related to observations in nasal polyps where increased albumin deposition has been thought to be caused by eosinophil-driven inflammation 15 . The expression of neutrophilic and proinflammatory cytokines has been observed previously in Chinese nasal polyp patients 9 and more specifically in Chinese nasal polyp patients that were IL-5/IL-17/IFN-γ negative 22 .…”
Section: Discussionmentioning
confidence: 81%
“…The association of albumin with eosinophil products can be related to observations in nasal polyps where increased albumin deposition has been thought to be caused by eosinophil-driven inflammation 15 . The expression of neutrophilic and proinflammatory cytokines has been observed previously in Chinese nasal polyp patients 9 and more specifically in Chinese nasal polyp patients that were IL-5/IL-17/IFN-γ negative 22 .…”
Section: Discussionmentioning
confidence: 81%
“…The pathogenesis of CRSwNP involves complex inflammation regulated by various chemical mediators and (Jareoncharsri et al 2002) showed that 81.9% of NP was neutrophilpredominant, supported by study done in China (Ba et al 2011). This suggested that Asian population might have different pathological mechanism from Caucasian population.…”
Section: Discussionmentioning
confidence: 99%
“…However, research studies conducted in India and Asian countries showed that about 48-69% of NP was neutrophil predominant and had lower cases of eosinophil-predominant NP compared to the Caucasian studies (Dafale et al 2012;Hao et al 2006;Ba et al 2011). A study showed 17% of the sample were in combination of eosinophil and neutrophil, and 27% of NP had high level of mast cell, suggesting that the pathogenic mechanism of NP involved a complex inflammation included other inflammatory cells (Hao et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Non-eosinophilic CRSwNP always presents with neutrophil-predominant inflammation (6). The subgroups have a variety of pathogeneses and may require different therapeutic options.…”
Section: Introductionmentioning
confidence: 99%